A-eye: Automated 3D MRI segmentation and morphometric feature extraction for eye and orbit atlas construction - Jaime Barranco; Adrian Konstantin Luyken; Yiwei Jia; Hamza Kebiri; Philipp Stachs; Pedro M. Gordaliza; Oscar Esteban; Yasser Aleman; Raphael Sznitman; Felix Streckenbach; Oliver Stachs; Sönke Langner; et al. (PLoS ONE, 2026)
In this study we introduce automated 3D segmentation of the healthy human adult eye and orbit from Magnetic Resonance Images, to improve ophthalmic diagnostics and treatments. Past efforts have primarily focused on small sample sizes and varied imaging modalities. Here, we leverage a large-scale dataset of T1-weighted MRI of 1245 subjects and the deep learning-based nnU-Net for MR-Eye segmentation tasks. The results showcase robust and accurate 3D segmentation of lens, globe, optic nerve, rectus muscles, and orbital fat. We also present the automated estimation of key ophthalmic morphometry biomarkers such as axial length and volumetry, while benchmarking correlations between body mass index and eye structure volumes. Quality control protocols are introduced through the pipeline to ensure the reliability of the segmented large-scale data, further enhancing the applicability of our algorithm in clinical research. As a major outcome we provide the first large-scale unbiased eye atlases (female, male, and combined) towards standardization of spatial normalization tools for MR-Eye.